Practice of lipoprotein apheresis and short-term efficacy in children with homozygous familial hypercholesterolemia: Data from an international registry. (April 2020) - Luirink, Ilse K.; Hutten, Barbara A.; Greber-Platzer, Susanne; Kolovou, Genovefa D.; Dann, Eldad J.; de Ferranti, Sarah D.; Taylan, Christina; Bruckert, Eric; Saheb, Samir; Oh, Jun; Driemeyer, Joenna; Farnier, Michel; et al.
Abstract: Background and aims: Homozygous familial hypercholesterolemia (hoFH) may cause life-threatening atherosclerotic cardiovascular disease in childhood. Lipoprotein apheresis (LA) is considered a pivotal treatment option, but data on its efficacy, safety and optimal performance are limited. We therefore established an international registry on the execution and outcomes of LA in HoFH children. Here we report LA policies and short-term outcomes. Methods: We approached centers worldwide, involved in LA in children with hoFH for participation. We collected information on clinical and treatment characteristics on patients aged 0–19 years between November 2016 and November 2018. Results: We included 50 children, treated at 15 sites. Median (IQR) LDL-C levels at diagnosis, on medication and on LA were 19.2 (16.2–22.1), 14.4 (10.8–16.7) mmol/L and 4.6 mmol/L, respectively. Median (IQR) time between diagnosis and start of LA was 2.8 (1.0–4.7) years. Six (12%) patients developed cardiovascular disease during that period. Most children received LA either weekly (43%) or biweekly (37%). Seven (17%) patients reached mean LDL-C levels <3.5 mmol/L, all of them treated at least weekly. Xanthomas were present in 42 (84%) patients at diagnosis and disappeared completely in 19 (45%) on LA. Side effects of LA were minor. There were significant differences in LA conduction between sites in terms of frequency, responsible medical specialities and vascular access. Conclusions: LA is a safe treatment and may effectively lower LDL-C in children with HoFH. However, there is room for improvement with respect to time of onset and optimization of LA therapy in terms of frequency and execution. Graphical abstract: Image 1 Highlights: Lipoprotein apheresis (LA) is safe in children with hoFH with a paucity of side effects. LA leads to an important reduction of LDL-C and xanthomas in children with hoFH. Only a small number of children with hoFH reach treatment goals on LA. There are important differences in LA conduction strategies between different sites.